Complement‐mediated inhibition of adiponectin regulates perivascular inflammation and vascular injury in hypertension. Issue 3 (14th December 2016) - Ruan, Cheng-Chao; Ma, Yu; Ge, Qian; Li, Yan; Zhu, Li-Min; Zhang, Ying; Kong, Ling-Ran; Wu, Qi-Hong; Li, Fanghong; Cheng, Lixian; Zhao, Allan Z.; Zhu, Ding-Liang; et al.
ABSTRACT: Perivascular adipose tissue (PVAT)‐derived adiponectin (APN) is a secreted adipokine that protects against hypertension‐related cardiovascular injury. However, the regulation of APN expression in hypertension remains to be explored. In this study, we demonstrated that down‐regulation of APN was associated with complement activation in the PVAT of desoxycorticosterone acetate (DOCA)‐salt hypertensive mice. Complement 3‐deficient hypertensive mice were protected from ANP decrease in the PVAT. APN deficiency blockaded the protective effects of complement inhibition against hypertensive vascular injury. Mechanistically, complement 5a (C5a)‐induced TNF‐α secretion from macrophages is required for inhibiting APN expression in adipocytes. Macrophage depletion reversed C5a agonist peptide‐induced TNF‐α up‐regulation and APN down‐regulation in the PVAT of DOCA mice. Moreover, we detected increased macrophage infiltration and C5a expression associated with decreased APN expression in adipose tissue from patients with aldosterone‐producing adenoma. These results identify a novel interaction between macrophages and adipocytes in the PVAT, where complement‐mediated inhibition of APN acts as a potential risk factor for hypertensive vascular inflammation.—Ruan, C.‐C., Ma, Y., Ge, Q., Li, Y., Zhu, L.‐M., Zhang, Y., Kong, L.‐R., Wu, Q‐H., Li, F., Cheng, L., Zhao, A. Z., Zhu, D.‐L., Gao, P.‐J. Complement‐mediated inhibition of adiponectin regulates perivascular inflammation and vascular injury in hypertension. FASEB J. 31, 1120–1129 (2017). www.fasebj.org